Barriers and advantages of Lean Manufacturing from the assessment of the maturity degree for organizational development and performance - Santos, Elenilson Rivando dos; Silva, Diewelly Maria; Almeida, Gláucia Regina de Oliveira (Brazilian Journal of Production Engineering, 2022)
Lean Manufacturing (LM) is a methodological approach that uses management tools and aims, mainly, at modifying traditional production models to new approaches that better manage processes from the current system. Thus, the assessment of the degree of maturity and adherence of the tools is little studied, mainly because of the complexity demonstrated. This research aims to carry out a systematic and bibliometric mapping of the barriers and advantages presented in the LM and their influence for the assessment of the maturity of the tools used, using the sample space between 2011 and 2021 in the Scielo, Scopus and Web of Science. A total of 27 articles relevant to the topic were selected that made up the portfolio of articles. In general, the works presented the systematization of barriers to LM in four aspects, the technical, work organization, human factors and the external environment, having the socio-technical foundation as a decision-making factor for the maintenance of organizational improvement practices proposed by the LM in the long term, thus ensuring the maturity of the tools used. Finally, although barriers exist in greater quantity, the advantages of LM give greater relevance to the topic studied, allowing for the continuity of research on the topic.